PENDIDIKAN KESEHATAN DAN DEMONSTRASI PENGOLAHAN BUAH NAGA UNTUK KESTABILAN KADAR HAEMOGLOBIN PADA IBU HAMIL - Wahyu Riniasih; Mingle A Pistanty; Festy Mahanani M; Kharisma Rahmawat; Sintia Ardiane Suyatmo; Wiwik Windiyartin (LPPM AN Nuur, 2023)
Background: Anemia is a condition of reduced red blood cells (erythrocytes) in blood circulation or haemoglobin (HB) period so that it is unable to fulfill its function as a carrier of oxygen throughout the body. Based on the results of Basic Health Research (Riskesdas) in 2013 in Indonesia, the prevalence of anemia in pregnant women was 37.1%, and in 2018 now the prevalence rate of anemia is 48.9%, increasing from 2013. Natural ingredients that can be used as an alternative to treat anemia and are easily obtained and cultivated also contain protein, vitamin C, and iron. and increased hemoglobin one of which is dragon fruit Mature dragon fruit contains many organic acids, proteins, minerals such as potassium, magnesium, calcium, iron, and vitamin C. Methodology: The subjects in this activity were pregnant women in Dusun Kranggan, Dusun Nonang, Dusun Glonggong, dan Dusun Sukorejo, Desa Krangganharjo, Kecamatan Toroh, Kabupaten Grobogan Provinsi Jawa Tengah. This activity will be held on Thursday, January 25, 2024. Results: The knowledge of the subject (pregnant women in Krangganharjo village) increased, which was initially unknown about the benefits of iron and what foods contain iron and how it is processed became known. There was an increase before and after the completion of health education in the range of 70%. Conclusion: The knowledge of the subject (pregnant women in krangganharjo village) increased, which was initially unknown about the benefits of iron and what foods contain iron and how it is processed became known.